Normalization of quantities of various dimensions - Ginevičius, Romualdas (Journal of Business Economics and Management, 2008)
Currently used methods of multiple criteria evaluation (MEM) based on the values obtained allow us to establish the priority order of the considered object's alternatives. However, they do not allow us to determine the values of multicriteria evaluation of a particular alternative taken out of their context. This restricts the range of MEM applications. To expand the application area of the methods, we should know how the criteria of a particular alternative describing the object considered which are expressed in different dimensions, can be normalized. This can be achieved by dividing any different value by the respective quantity of the same dimension. The task is complicated by the fact that these quantities should be comparable for all the criteria.First published online: 14 Oct 2010